The Effect of Different Types of Separating Medium On Some Physical Properties of Processing Acrylic Denture-base with Two Investment Materials: A comparative Study - mohammed, Nihad (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): In the present study, glycerin is used as a substitute for tin-foil and cold mold seal (Alginate mould seal) in the process of curing heat and cold-cure acrylic resin denture base against stone and plaster. Methodology: 60 specimens were prepared from heat-cure acrylic resin and cold-cure acrylic resin denture base. The study includes 12 groups of specimens depending on the type of processing, investment material and type of separating medium that are used in curing process. Each group of them contains 5 specimens for each test. Some of physical properties of the processed acrylic denture base that (water sorption and solubility) have been compared with those processed using tin-foil and tin-foil substitute. Results: The results have shown that tin-foil is still the best separating medium that is used due to the best properties obtained when using tin-foil as a separating medium, while no significant differences have been observed between glycerin and cold mold seal specimens in respect to water sorption and solubility of the testing groups. Recommendations: that glycerin can be considered as a satisfactory separating medium for both heat and cold-cured acrylic denture base resins, especially because it is easy to get, easy to use and cheap.